2019
DOI: 10.1002/jcla.22964
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index, neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio can predict clinical outcomes in patients with metastatic non‐small‐cell lung cancer treated with nivolumab

Abstract: Background Explore markers to predict the clinical outcomes of checkpoint inhibitors have high unmet needs. The following study investigates whether hematologic parameter such as systemic immune‐inflammation index (SII), neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR) is associated with nivolumab efficacy in advanced non‐small‐cell lung cancer (NSCLC). Methods Advanced/metastatic NSCLC patients treated with nivolumab monotherapy for second‐line or further‐line treatment at Jilin Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
151
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 53 publications
(54 reference statements)
5
151
0
2
Order By: Relevance
“…Influenza virus infection induced a relatively increased N count and a relatively decreased L count, which was different from the changes caused by other common viruses such as adenovirus, respiratory syncytial virus, EB virus, human herpes virus type 6, and enterovirus . In addition, NLR was as a more sensitive parameter for influenza virus infection than the other cell count parameters in our study, which was consistent with reports on many other diseases, such as lung cancer and swine flu . A hemogram is a basic investigation performed in all admitted patients (including patients with respiratory tract infection), and NLR can be easily calculated from the results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Influenza virus infection induced a relatively increased N count and a relatively decreased L count, which was different from the changes caused by other common viruses such as adenovirus, respiratory syncytial virus, EB virus, human herpes virus type 6, and enterovirus . In addition, NLR was as a more sensitive parameter for influenza virus infection than the other cell count parameters in our study, which was consistent with reports on many other diseases, such as lung cancer and swine flu . A hemogram is a basic investigation performed in all admitted patients (including patients with respiratory tract infection), and NLR can be easily calculated from the results.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, antigen tests have poor sensitivity to some influenza viruses . Recently, it was reported that hematological inflammatory indexes based on blood cell analysis had an important predictive value for the prognosis of infections, cancers, and many other diseases . This study aimed to conduct a retrospective analysis of hematological inflammatory parameters (eg, neutrophils, lymphocytes, platelets) and blood cell count indexes, particularly the NLR, in hospitalized patients with suspected influenza.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of different biomarkers in a single prognostic score rather than focusing on a single biomarker permits to better identify patients who most likely will (or will not) benefit from ICIs [13]. Many immune-based prognostic scores were studied using clinical features and blood biomarkers such as lung immune prognostic index (LIPI) [50], advanced lung cancer inflammation index (ALI) [59], immunotherapy sex-ECOG-NLR-delta NLR (iSEND) [60], systemic inflammation index (SII) [18,61] and aggregate index of systemic inflammation (AISI) [61]. All these scores incorporated NLR and most of them included ECOG PS and LDH.…”
Section: Discussionmentioning
confidence: 99%
“…The LIPI score from Mezquita et al was the only one with a validation set of patients treated with ICIs and a control cohort of patients treated with chemotherapy alone in the same setting [50]. Moreover, some of the reported scores were not associated with survival at baseline [50,59,61] but only at time-series analysis (i.e., at 6 weeks of treatment) [18].…”
Section: Discussionmentioning
confidence: 99%
“…All statistical tests were two-sided, and p-values < 0.05 were regarded as statistically significant. The cutoff values for body mass index (BMI), albumin, lactate dehydrogenase (LDH), neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR), and C-reactive protein (CRP) following prior therapy were determined according to previous reports [10][11][12][13][14][15]. The PFS and OS were calculated using the Kaplan-Meier method, and differences were compared using the log-rank test.…”
Section: Discussionmentioning
confidence: 99%